2018
DOI: 10.1093/ons/opy342
|View full text |Cite
|
Sign up to set email alerts
|

Technical Aspects and Operative Nuances Using a High-Definition 3-Dimensional Exoscope for Cerebral Bypass Surgery

Abstract: BACKGROUND Cerebral bypass operation is a technically challenging operation that requires excellent surgical visibility and efficient ergonomics to minimize complications and maximize successful revascularization. Despite the operative microscope's utilization for the past two generations, there remains a need for continued improvement in operative visualization and surgical ergonomics. OBJECTIVE To report the positives and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 10 publications
1
43
1
Order By: Relevance
“…While no neurovascular surgeries were performed in our study, other studies have shown those procedures feasible for exoscopic surgery as well [11]. Apart from the use in neurosurgery, ENT surgeons have reported success and high satisfaction [1,14].…”
Section: Discussionmentioning
confidence: 65%
“…While no neurovascular surgeries were performed in our study, other studies have shown those procedures feasible for exoscopic surgery as well [11]. Apart from the use in neurosurgery, ENT surgeons have reported success and high satisfaction [1,14].…”
Section: Discussionmentioning
confidence: 65%
“…[17] Several skull-base neurosurgeons performing intranasal endoscopic surgery have demonstrated that lack of stereopsis does not prevent from achieving satisfactory surgical outcomes. [20] Notwithstanding, the 3D exoscope is promising innovative equipment, which has just been evaluated in the cranial and spinal procedure in the last 2 years, [21][22][23][24][25][26] clinical data comparing the 2D and 3D version in the setting of neurosurgical operation was lacking. In this study, we demonstrated that the 2D exoscope had a potentially comparable operational efficacy and safety, even with much less bleeding volume, as the operating microscope (OM) in large VS resection, which requires high handeye coordination.…”
Section: Discussionmentioning
confidence: 99%
“…It took about nine years to further evolve the 2D visualization and introduce the first 3D exoscopic visualization system [39,40] . In the following years, the 3D exoscope has been used to perform various technical more demanding neurosurgical procedures, even in pediatric cases, including treatment of cerebrovascular disorders (i.e., aneurysm clipping and bypass surgery), degenerative spinal disorders, and resection of cranial and spinal tumors [41][42][43][44][45][46][47][48][49][50] . VITOM®-3D (Video Telescopic Operating Microscope, Karl Storz GmbH & Co. KG, Tuttlingen, Germany), provides a 3D visualization in ultra-high definition (4K) quality, with a focal length of 20-50 mm and magnification ranges from 8× to 30×.…”
Section: Exoscope In Neurosurgerymentioning
confidence: 99%
“…The published literature reveals the increased interest in the application of exoscopic visualization in neurosurgery, with the vast majority of articles being published within the last two years [46,48,49,[51][52][53][54][55] . Thanks to literature contributions, it became possible to analyze the advantages and limitations of Vitom-3D.…”
Section: Exoscope In Neurosurgerymentioning
confidence: 99%